Construction of i-KCare: kidney failure self-care multimedia courseware / Arifah Fasha Rosmani and Nur Atikah Adzman - Rosmani, Arifah Fasha; Adzman, Nur Atikah (UiTM Cawangan Perlis, 2017)
Kidney failure is a condition where the kidney is unable to function normally. Currently, most of kidney failures patients are not aware of the importance of at home self-care and this may affect their health and consequently, sooner or later it will decline. The patients should be conscious of their proper diet, daily activities that they can perform, and other related information to avoid their kidney from worsening. The kidney failure patients need to understand all this information to help them in taking care of themselves at home. Thus, this multimedia courseware is designed and constructed for these patients to increase their knowledge and awareness on the disease. This project has applied one of the System Development Life Cycle (SDLC) models, which is Prototype Model and it had been tested using Acceptance Test and Heuristic Test. The participants for the tests are kidney failure patients, their family members, and nurses in dialysis centers. This courseware is expected to increase their knowledge and awareness on the disease, hence, helping them to have a better self-care at home.